Accommodation facilities in northern Turkey in the context of the COVID-19 pandemic - Hełdak, Maria; Kurt Konakoglu, Sultan Sevinc; Ramsey, David; Kurtyka, Izabela; Raszka, Beata (Bulletin of Geography. Socio-economic Series, 2026)
The aim of this study is to analyse and compare the situation of owners of accommodation facilities—guesthouses, hotels, guest rooms, and campsites—in Turkey across two distinct periods: the pre-pandemic period and the post-pandemic period, taking into account the current geopolitical context. The pandemic period itself was analysed; however, due to government-imposed restrictions and a substantial decline in occupancy rates of accommodation facilities (below 10%, outside the campsites), it was not possible to conduct reliable comparative analyses for this period. The specific objectives also include examining the relationship between the services and attractions offered by accommodation providers and occupancy rates. ...